The influence of sweet pepper pectin structural characteristics on cytokine secretion by THP-1 macrophages - do Nascimento, Georgia Erdmann; Winnischofer, Sheila Maria Brochado; Ramirez, Marcel Ivan; Iacomini, Marcello; Cordeiro, Lucimara Mach Côrtes (Food research international, 2017)
Pectins can modulate the biological responses interacting directly with immune cells. The observed responses can strongly be affected by polysaccharide structural features. We analyzed the intrinsic activation capacity of native and modified sweet pepper pectin on cytokine secretion by THP-1 macrophages as well as compare their effects in the presence of lipopolysaccharide. Modified pectin was obtained by partial acid hydrolysis which promoted the removal of side chains as well as the reduction of molecular weight and the degree of methyl esterification of native pectin. The results showed that both fractions had no effect on THP-1 viability. Native pectin at 300μg/mL increased TNF-α, IL-1β and IL-10 cytokine secretion by THP-1 macrophages. However, in the presence of lipopolysaccharide, it can attenuate the inflammatory response by reducing the production of the pro-inflammatory cytokines TNF-α and IL-1β and increasing the anti-inflammatory cytokine IL-10, as well as decreasing the TNF-α/IL-10 and IL-1β/IL-10 ratios. The structural modifications caused by acid hydrolysis affected the intrinsic activation capacity of native pectin to modulate the cytokines secretion. These results indicate that degree of methyl esterification, molecular weight and presence of side chains are important structural features of pectins involved in the modulation of cytokine secretion by THP-1 macrophages. [Display omitted] •The impact of structural differences of pectin on cytokine secretion was evaluated.•Removal of sweet pepper pectin side chains by partial acid hydrolysis was performed.•Sweet pepper pectins stimulated TNF-α, IL-1β and IL-10 secretion by THP-1 macrophage.•The removal of pectin side chains altered the cytokine secretion profile.•Both native and modified pectins attenuated the inflammatory response triggered by LPS stimulation.